Lesbian health : current assessment and directions for the future - Solarz, Andrea L. (National Academy Press, 1999)
Women's health, as a field of study, is a developing discipline. Health theories in general have been based on studies of men. However, in recent years, more attention has shifted to women's health, realizing the disparities between men and women in relation to their health. During the last two decades, a similar shift has occurred for a group of women -- lesbian women -- to further identify and specify their health needs.
Report based on a workshop held in Oct. 1997.
Keywords: Lesbians -- Health and hygiene.; Lesbians -- Health and hygiene -- Government policy -- United States.; Women -- Health and hygiene.; Lesbianism.; Homosexuality, Female; Women's Health; United States; Lesbiennes -- Santé et hygiène.; Lesbiennes -- Santé et hygiène -- Politique gouvernementale -- États-Unis.; Femmes -- Santé et hygiène.; Lesbianisme.; MEDICAL -- Preventive Medicine.; HEALTH & FITNESS -- Healthy Living.; HEALTH & FITNESS -- Reference.; HEALTH & FITNESS -- Holism.; Women -- Health and hygiene; Lesbians -- Health and hygiene; Homosexualité féminine -- États Unis d'Amérique.; Santé publique -- États Unis d'Amérique.; Santé des femmes -- États Unis d'Amérique.